2016
DOI: 10.16965/ijar.2016.403
|View full text |Cite
|
Sign up to set email alerts
|

A Morphological Study on Fallopian Tube

Abstract: Background and Aims: The fallopian tubes, also known as, uterine tubes, are pair of fine tubes leading from the ovaries of female mammals into the uterus, via the uterotubal junction. Optimal fallopian tube function is necessary to provide a proper environment for early human life. Fallopian tube plays an essential role in gamete transport, fertilization and the early development of the embryo which can be affected by a wide range of factors and conditions that may impair fertility. The study of normal morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 2 publications
1
9
1
Order By: Relevance
“…A third case describes an incarcerated mobile cecum resulting from an internal herniation through a loop created by an elongated left fallopian tube of 25 cm [5]. While the patient illustrated in this case presents similarly to our patient, our patient's right fallopian tube was 9.5 cm in length by 0.7 cm in diameter, which is closer to the average length of fallopian tubes seen in females in their 70s of 8.8 cm [7]. The distal portion of the right fallopian tube was found with atypical adhesions that connected it to the retroperitoneum.…”
Section: Discussionsupporting
confidence: 58%
“…A third case describes an incarcerated mobile cecum resulting from an internal herniation through a loop created by an elongated left fallopian tube of 25 cm [5]. While the patient illustrated in this case presents similarly to our patient, our patient's right fallopian tube was 9.5 cm in length by 0.7 cm in diameter, which is closer to the average length of fallopian tubes seen in females in their 70s of 8.8 cm [7]. The distal portion of the right fallopian tube was found with atypical adhesions that connected it to the retroperitoneum.…”
Section: Discussionsupporting
confidence: 58%
“…The unusual length of the patient's left fallopian tube is perplexing. The average length of a fallopian tube in 60-year-old women is less than 10 cm [21] whereas the length left fallopian tube in this patient was 25 cm. The elongation of the fallopian tube runs counter to the progressive atrophy typically seen in fallopian tubes in postmenopausal women [22] , [23] .…”
Section: Discussioncontrasting
confidence: 56%
“…Whereas in the present study we got the highest and lowest mean value in the post reproductive group and pre reproductive age group but both were on the left side (5.24, 3.00cm respectively). 2 Hwang TS found that uterine tube length did not show statistically significant differences in relation to age. But in our study there was significant correlation of age with the length of fallopian tube on both right and left side as P value was 0.000.…”
Section: Discussionmentioning
confidence: 93%
“…The fallopian tube act as a passage for the germ cells in two directions and zygote towards the uterus. 2 Fallopian tubes is very important for fertility and it is most commonly involved in cases of human infertility. Proper fallopian tube function is very significant to provide correct environment for the initial stages of embryo.…”
Section: Introductionmentioning
confidence: 99%